GERAKAN OPINI DIGITAL : STUDI ANALISIS JARINGAN MEDIA SOSIAL #PERCUMALAPORPOLISI VS #POLRIPRESISI DI TWITTER - Deafrine Nabila Shalsabillah (2023)
Digital media ubiquity causes the online activity to increase. Digital Movement of Opinion is a prominent concept of digital activity. Digital media, like social media, provide the public with the means to express their own opinions. One of the most important issues to emerge on social media like as Twitter in order to significantly influence public opinion is the issue of Kepolisian RI. Using the hashtags #PolriPresisi for those who support the Kepolisian RI and #PercumaLaporPolisi for those who do not, this issue highlights the pro and con sides of society. The digital movement of opinion that formed on this issue created a large network. This research aims to describe the network structure on the issue of the Indonesian National Police on social media Twitter through the hashtags #PercumaLaporPolisi and #PolriPresisi in order to see the mobilization of digital movements of opinion on both networks. The research theory used in this thesis is the theory of digital opinion movement by using social media network analysis as the research method. The research shows that the hashtag #PercumaLaporPolisi perfoms better than the hashtag #PolriPresisi at mobilizing digital opinion, because the emotional hashtag and its concise frame are the reasons for its success. Besides that, the advantage of the hashtag #PercumaLaporPolisi is that the hashtag #PolriPresisi does not fulfill the 4 main characteristics of the Digital Movement of Opinion. The hashtag network #PolriPresisi only focuses on building reputation after the emergence of the hashtag #PercumaLaporPolisi which contained public disappointment with the Kepolisian RI.